A new species of Ibitermes (Isoptera, Termitidae) from the Atlantic forest, northeastern Brazil - Alexandre Vasconcellos (Iheringia: Série Zoologia, 2002)
The sterile castes of Ibitermes inflatus sp. nov. from Rio Tinto, State of Paraíba, Brazil are described and illustrated. This is the first record of a species of Ibitermes from the Brazilian northeast and from the Atlantic Forest biome. The absence of ridges in the molar plate of the left mandible and the presence of granules of sand and silt mixed with organic matter in advanced stage of decomposition in the digestive tube of workers suggest that the species is a typical humus feeding termite.